Aproveitamento da carne Wooden Breast e gordura abdominal de frango para elaboração de emulsionado tipo hambúrguer - Santos, Miriane Moreira Fernandes (2019)
The study aims to evaluate the effect of wooden chicken breast and abdominal fat on the oxidative stability and quality of emulsified product type patties under freezing temperatures (18 ° C) for 90 days. First, it was determined the lipid content and fatty acid profile of the chicken by-products (abdominal fat and skin). Four treatments were developed: PNS (emulsified with normal breast and skin), PNF (emulsified with normal breast and abdominal fat), PWB (emulsified with wooden breast), PNW (normal breast and wooden mixture). After processing the emulsified type patties, the hygienic-sanitary conditions of the product were evaluated, which was later characterized by the determinations of the partial chemical composition (moisture, proteins, lipids and ash), pH, Aw, performance during cooking (yield, shrinkage, shortening, water retention), texture profile, color parameters (L *, a *, b *, E, Hue) and sensory analysis (acceptance test and purchase intention). The effect of the storage was analyzed through the analysis of the color parameters (L *, a *, b *), hardness, shear force, fatty acid profile, volatile compounds and color and aroma degradation evaluated by untrained judges. The development of lipid oxidation was measured by peroxide index, TBARs, paraanisidine analysis. For protein oxidation, the analysis of carbonyl compounds was carried out. Emulsified type patties were microbiologically safe because they presented levels of microorganisms were below those determined by Brazilian legislation. The type of chicken breast used in the preparation of the emulsified type patties did not influenced ash, lipids, Aw, shrinkage, shortening, b*, E, acceptance and intention to purchase the product. The storage time promoted a lower hardness in the product processed with the mixture of normal chicken breast and wooden chicken breast, also influenced the lipid oxidation, but the judges did not perceive difference in color and aroma during the 90 days. About the protein oxidation, the storage period had fewer affect on the emulsified made with the mixture of normal breast and wooden breast. Regarding abdominal fat and skin, the higher lipid content was found for abdominal fat, as well as higher presence of polyunsaturated fatty acids. The type of fat used in the development of emulsified type patties influenced moisture, lipids and L *. The storage time promoted changes in the fatty acid profile, volatile compounds and the texture profile of the product. Is a highlighted in the fatty acids profile, the predominance of monounsaturated fatty acids, in the volatile compounds, the low presence of lipid oxidation markers and, concerning the texture profile, the lowest hardness and shear force was for products processed with abdominal fat. The results produced in this research indicate that it is possible to use the wooden chicken breast and it is abdominal fat in the production of emulsified type patties. Although there is levels of oxidation throughout the storage of the product, these can be considered low and not perceivable by consumers.